Experimental validation of a 2D–3D conversion method for estimation of multiple 3D characteristics of discrete elements. (22nd February 2020) - Ueda, Takao
Abstract: Accurate assessment of three-dimensional (3D) characteristics, such as the shape and size distribution, of discrete elements (e.g. particles, granules, grains, voids, crystals, cells and fibers) is required in various fields. But generally, in practice, two-dimensional (2D) instead of 3D assessment is conducted due to limitations in time, cost or measurement technology (as in microscopic observation of discrete elements). In this study, experimental validation was conducted for a 2D–3D conversion method, developed in 2018, which estimates multiple 3D parameters based on 2D counterparts, using an x-ray computed tomography analysis of silica sand. Six 3D parameters (volume, surface area, long-axis length, sphericity and long/middle and long/short axis ratios) were successfully estimated based on five measured 2D parameters (sectional area, perimeter, long-axis length, circularity and long/short axis ratio). Abstract : An experimental validation was conducted for a 2D–3D conversion method, which estimates multiple 3D parameters based on 2D counterparts, using X-ray computed tomography analysis of silica sand. Six 3D parameters (volume, surface area, long-axis length, sphericity, long/middle and long/short axis ratio) were successfully estimated based on measured 2D parameters.